2020
DOI: 10.3389/fped.2020.00349
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bronchopulmonary Dysplasia in Preterm Infants Using Postnatal Risk Factors

Abstract: Objective: To identify postnatal risk factors for bronchopulmonary dysplasia (BPD) development in preterm infants with gestational age ≤32 weeks. Methods: Seventy-two preterm infants(30 with BPD and 42 non-BPD controls) admitted in the neonatal intensive care unit (NICU) of the Children's Hospital of Soochow University during 2017 were enrolled in this prospective longitudinal study. Perinatal clinical data, a neonatal critical illness score (NCIS), different soluble B7-H3(sB7-H3), and interleukin-18 (IL-18) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…In the current study, a higher ratio of enteral feeding/total fluid intake during the second week of life was significantly associated with a lower risk of BPD. This finding is consistent with the other two studies ( 18 , 21 ), although the population in our study was younger and smaller. However, Thiess ( 6 ) reported that enteral nutrition supply tended to be higher in the no/mild BPD group but without statistical significance after risk adjustment.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, a higher ratio of enteral feeding/total fluid intake during the second week of life was significantly associated with a lower risk of BPD. This finding is consistent with the other two studies ( 18 , 21 ), although the population in our study was younger and smaller. However, Thiess ( 6 ) reported that enteral nutrition supply tended to be higher in the no/mild BPD group but without statistical significance after risk adjustment.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous studies [14], the use of invasive ventilation in the BPD group is signi cantly higher compared with that in the non-BPD group. Also, previous research [23] indicated that infants on endotracheal tube for 4-7 days are likely to have BPD or death compared with NIPPV (p < 0.02) and NCPAP (p < 0.01) groups.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the advanced perinatal and neonatal care, the morbidity and mortality of BPD do not decrease. BPD can affect the survival rate of premature infants and the quality of life of survival of children profoundly and lastingly [14]. Multiple studies showed that preterm infants with BPD continue to have impaired lung function later in the childhood and increased chance of developing asthma [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the discrimination accuracies of the method were 0.76, 0.84, and 0.86 on days 4, 7, and 10, respectively. Li Ding et al built a model involving neonatal critical illness score, enteral feeding ≥40 days after birth and other factors ( 25 ). The ROC curve showed a high AUC value of 0,96.…”
Section: Discussionmentioning
confidence: 99%